Characterization of Advanced Encryption Standard (AES) for Textual and Image data (International Journal of Engineering and Computer Science, 2016)
— Safekeeping of multimedia data is an imperious concern for the reason that fast progression of    digital data exchanges (DDE) over unsafe network. Multimedia data safety is accomplished by methods of cryptography, which is concerned with encryption of data. Standard symmetric encryption algorithms are responsible to enhance security for the multimedia data. The problem of computational head is always on the way. To overwhelmed  that  delinquent, we examine  the Advanced  Encryption  Standard  (AES)  and  amend  it, to diminish  the calculation of algorithm and for enlightening the encryption performance. In this paper, an improved AES algorithm has been investigated. As an alternative of using Mix column we practice with modified step, takes a stable modified step key Mk, and perform expansion routine by using Randal’s key schedule to generate a modified step schedule. When the Mk length is 128 bit, then the Expansion generates a total 11 sub Mk arrays of 128 bits, and Xor with state array in every rounds except final round. Hypothetical analysis and experimental results provide evidence that this technique has the capability of high speed as well as fewer overheads on data. Modified-AES algorithm is a quick trivial encryption algorithm for security of multimedia data. All above advantages put together algorithm highly appropriate for the images and plain text transfer as well.